The first results of a 6-year follow-up study of a patient with early psoriatic arthritis treated with a treat-to-target strategy - P. O. Tremaskina; E. Yu. Loginova; T. V. Korotaeva; A. V. Sukhinina (Современная ревматология)
The paper characterizes the basic principles of a treat-to-target (T2T) strategy for spondyloarthritis, including psoriatic arthritis (PsA). The data from observational cohort studies suggest that inadequate therapy for PsA increases the risk of structural progression. The results, obtained in the international randomized controlled Tight Control of Psoriatic Arthritis (TICOPA) trial and the Russian open-label observational REMARCA study, have justified the necessity of using the T2T strategy for early-stage PsA. The authors have analyzed their own results of a 6-year follow-up study of a patient with early PsA, in whom the T2T strategy was used.